2020
DOI: 10.1371/journal.pgen.1009228
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting codon usage identifies intensity-specific modifiers of Ras/MAPK signaling in vivo

Abstract: Signal transduction pathways are intricately fine-tuned to accomplish diverse biological processes. An example is the conserved Ras/mitogen-activated-protein-kinase (MAPK) pathway, which exhibits context-dependent signaling output dynamics and regulation. Here, by altering codon usage as a novel platform to control signaling output, we screened the Drosophila genome for modifiers specific to either weak or strong Ras-driven eye phenotypes. Our screen enriched for regions of the genome not previously connected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 116 publications
1
14
0
Order By: Relevance
“…Rare codons limit protein translation efficiency 14,15 and optimizing codons in the KRAS gene locus did indeed result in higher KRAS protein expression 13 . Consistent with the sweet-spot model, higher KRAS expression reduced carcinogen-induced tumorigenesis in mice and altered engagement with cancer signaling pathways 13,16,17,18 . As a result, it was suggested that KRAS expression is optimal in most contexts, whereas HRAS and NRAS expression is too high 4,13 .…”
Section: Introductionsupporting
confidence: 54%
“…Rare codons limit protein translation efficiency 14,15 and optimizing codons in the KRAS gene locus did indeed result in higher KRAS protein expression 13 . Consistent with the sweet-spot model, higher KRAS expression reduced carcinogen-induced tumorigenesis in mice and altered engagement with cancer signaling pathways 13,16,17,18 . As a result, it was suggested that KRAS expression is optimal in most contexts, whereas HRAS and NRAS expression is too high 4,13 .…”
Section: Introductionsupporting
confidence: 54%
“…This locus is well-established to express transgenes at robust and reproducible levels (Markstein et al, 2008). As we have done previously (Sawyer et al, 2020), we placed all our transgenic reporters in the same vector backbone, which uses a ubiquitin promoter sequence for robust gene expression (Methods). In this way, we control for the effects of chromatin environment on gene expression and ensure that any differences in protein production are due to differences in coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study of codon-dependent effects of Ras signaling in Drosophila identified profound phenotypic differences of a 2-fold, codon-dependent increase in protein expression (Sawyer et al, 2020). We next examined the impact of increased, codon-dependent protein expression of RpL10Aa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single SF may regulate multiple AS events, and an AS event may also be regulated by multiple SFs. Ribosomal protein s21 (RPS21) is a ribosome-related protein, which has been shown to play an important role in ribosomal biogenesis and may affect the occurrence and development of osteosarcoma and prostate cancer through the RAS/MAPK pathway ( Arthurs et al, 2017 ; Fan et al, 2018 ; Liang et al, 2019 ; Sawyer et al, 2020 ; Wang et al, 2020 ). Through the query of the database GEPIA2, the expression of RPS21 gene is not significantly different in tumor and normal tissues ( Supplementary Figure 2C ), so its potential function in breast cancer has not been studied so far, but according to our research, one of the transcripts of RPS (AA- RPS21) is differentially expressed in cancer and normal tissues of breast cancer patients, which suggests that this transcript may play a tumor-driving role in breast cancer, so it is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%